Integrating PLUS and InVEST model to project carbon dynamics in China’s yellow river basin under multi-scenarios (1980–2100) - Chang, Zhongbing; Wang, Jiaming; Xiong, Xin; Jiang, Jun; Wu, Jianping; Chen, Songjia; Li, Jie; Zhang, Shuo; Ji, Guangxing; Qian, Baowei (Frontiers in Earth Science, 2025)
Predicting future land-use patterns and carbon storage is essential for understanding regional terrestrial ecosystems, as regional land-use change plays a crucial role in ecosystem carbon storage variations. Using the Patch-generating Land Use Simulation Model (PLUS), we simulated the 2020 land-use types in the Yellow River Basin (YRB) based on the 2010 data. Subsequently, we predicted YRB land-use types for 2030 to 2100. Finally, based on these simulated land-use patterns, we calculated the carbon storage in the YRB from 1980 to 2100 using the InVEST model. The results showed that: (1) From 1980 to 2020, the InVEST model showed that carbon storage in the Yellow River Basin (YRB) exhibited an increasing trend of 12.10%. Rapid carbon storage increases can be observed in 2000–2020 (16.9 million tons). The largest carbon storage was found in Grassland (2487.24 million tons), which accounts for 51.03% of the total carbon storage in YRB. (2) During 2030 to 2100, the grassland area showed a decrease trend in SSP1-2.6 (−12.22%). The forest area showed an increase trend in SSP1-2.6 (3.49%). (3) Among the different scenarios, SSP1-2.6 (103.99 million tons) and current scenarios (23.07 million tons) showed the largest carbon storage gains from 2030 to 2100, primarily attributed to the cultivated land and forest, despite a major loss from grassland. SSP2-4.5 showed a carbon storage loss of 23.48 million tons, while a slight gain of 6.49 million tons was observed under SSP5-8.5. (4) Carbon storage losses were primarily observed in the grassland-dominated northern regions of the YRB. In contrast, the southernmost and eastern regions showed an increasing trend. This research provides essential scientific support for optimizing land-use structure and enhancing land management strategies across the YRB basin.